Image-guided Intraarticular Hip Injections and Risk of Infection After Hip Arthroscopy (141). Issue 10 (31st October 2021) - Varady, Nathan; Ameen, Troy; Chopra, Ahab; Kucharik, Michael; Abraham, Paul; Freccero, David; Smith, Eric; Martin, Scott
Objectives: Intraarticular injections are fundamental in the diagnosis and treatment of many types of hip pathology. However, there are conflicting data about their safety ≤3 months prior to hip arthroscopy. One large database study demonstrated over a two-fold increase in infection risk (with infection rates far higher than what is typically seen clinically [>1-2%]), while a recent institutional study reported 0 infections in a series of 500 patients undergoing injection within 3 months of arthroscopy. An important difference between these works was the use of image-guidance, with the former not evaluating this factor and the latter including only ultrasound (US)-guided injections. In fact, despite the growing use of US-guided hip injections, no prior study has compared the risk of complications, including infection, between US and fluoroscopic (FL)- guided hip injections prior to hip surgery. Therefore, the purposes of this study were to assess the risk of infection associated with image-guided intraarticular injections prior to hip arthroscopy and compare that risk between US and FL- guidance. Methods: This was a retrospective cohort study of patients undergoing hip arthroscopy in a large commercial claims database (MarketScan) from 2007-2017. Patients were required to have 1-year of continuous enrollment prior to and 6-months after hip arthroscopy. Patient age, sex, geographic region, medical history, surgical details, and hip injections (including image- guidance, timing, and laterality) were collected. For both the US and FL cohort, patients who underwent injection ≤3 months preoperatively and >3-12 months preoperatively were compared to those who did not undergo preoperative injection. Patients with both types of injections, with an infection diagnosis at the time of index injection, or with missing laterality data were excluded. The primary outcome of this study was surgical site infection within 6 months of surgery. Chi-squared or Fisher's exact tests and multivariable logistic regressions were used to assess the association between preoperative hip injection and infection. Finally, we performed sensitivity analyses that did not exclude patients with an infection at time of hip arthroscopy. Results: We identified 17, 093 hip arthroscopy patients (mean [SD] age 37.2 [14.0] years; 14, 685 [85.9%] no injection control patients and 2, 408 [14.1%] patients who underwent hip arthroscopy within 12-months of image-guided hip injection) (Table 1). In the FL cohort (n=1, 219 [50.7%]), 673 (55.2%) patients underwent hip arthroscopy ≤3 months after hip injection, while 546 (44.8%) patients underwent hip arthroscopy >3-12 months following hip injection. Similarly, for the US cohort, 673 (56.6%) patients underwent hip arthroscopy ≤3 months after their hip injection, while 516 (43.4%) patients underwent hip arthroscopy >3-12 months following hip injection. Patients undergoing FL-guided (0.55%) and US-guided (0.58%) hip injection >3-12 months prior to hip arthroscopy had similar infection rates as those who did not undergo intraarticular injection in the 12 months prior to hip arthroscopy (0.50%, p=0.76 and p=0.75, respectively) (Table 1). Similarly, the infection rates for patients undergoing US-guided (0.45%) and FL-guided (0.45%) injections in the 3-months prior to arthroscopy were not significantly different from control patients who did not undergo preoperative hip injection (0.50%, p=1 for both). Results held in adjusted analysis controlling for age, sex, geography, year, smoking, and comorbidities. In reference to the no injection cohort, the adjusted odds ratio (95% CI) of postoperative infection for patients undergoing FL-guided injection ≤3 months and >3-12 months prior to hip arthroscopy were 0.90 (0.28-2.94, p=0.87) and 1.17 (0.36-3.84, p=0.80), respectively. For US-guided injection, the adjusted odds ratios at ≤3 months and >3-12 months were 0.89 (0.28-2.87, p=0.84) and 1.11 (0.34-3.60, p=0.86), respectively. Notably, infection rates in the arthroscopy ≤3 months cohort were substantially higher when including patients with an infection at the time of hip arthroscopy (FL 1.18%, US 0.74%). Conclusions: Postoperative infection following intraarticular hip injection ≤3 months prior to hip arthroscopy is rare (<0.5%) and no more common than in patients who did not undergo preoperative injection. Moreover, there do not appear to be substantial differences in infection risk between imaging-modalities. Notably, postoperative infection rates were substantially higher in sensitivity analyses where we did not exclude patients who had an infection at the time of the hip injection/aspiration. As the common procedural code for hip injections also includes aspirations, the elevated rates seen in the prior large database study were likely due to the 'injections' being aspirations of infected joints that then underwent arthroscopy[VNH1] . In conclusion, in the largest ever sample of patients undergoing hip injections prior to hip arthroscopy, hip injection ≤3 months prior to hip arthroscopy was not associated with increased infection risk for either US- or FL-guided injections.